(3cJGH eGdGjSY aj Yde GdWHs ((3eOjfI GdbSWfWjfjI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi dGjcJHg MbjbI eYQaI GdYdhe hGdCagGe hHYO aEfg deG cGf GdEfSGf Hd GdMjhGf LedI ef GdeQcHGJ GdYVhjI s
(3BNQgG (B:s
(3hNUhUkG eG ZPG CVja Zdjg TF ef ZjQ Cf jchf YUGQI eWHhNI abW s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdWHs